Landsenses ecological planning for the Xianghe Segment of China's Grand Canal. Issue 4 (3rd July 2016) - Dong, Rencai; Liu, Xin; Liu, Miaoling; Feng, Qiyuan; Su, Xiaodan; Wu, Gang
ABSTRACT: Traditional methods of urban planning mainly focus on urban land, population size and transport priorities, and fail to consider environmental quality and welfare. To build a suitable urban form for future residents, urban eco-planners should consider the various data and technologies available, especially a resident's sensitivity in their planning. Rational and scientific planning needs comprehensive analysis of urban ecosystems, including both natural and human factors. The new concept and theory, 'landsenses', can help urban planners to integrate human sensitivity into their blueprint. Excellent eco-planning should include all forms of human senses, that is sight, hearing, taste, smell and touch. Based on the framework of landsenses ecology, we tentatively made a landsenses ecological planning for the Xianghe Segment of China's Grand Canal (XSCGC), in which we addressed the importance and challenges to incorporate a resident's sensory information into the ecological planning process, to promote the use of mix-marching data and the Internet of Things.